Client experiences with holistic neuropsychological rehabilitation: "It is an ongoing process". Issue 8 (14th September 2022) - Domensino, Anne-Fleur; Verberne, Daan; Prince, Leyla; Fish, Jessica; Winegardner, Jill; Bateman, Andrew; Wilson, Barbara; Ponds, Rudolf; van Heugten, Caroline
ABSTRACT: The effectiveness of holistic neuropsychological rehabilitation for people with acquired brain injury has previously been demonstrated by means of standardized and routinely administered outcome measures. However, the most important outcomes from the perspective of former clients are largely unknown. This study explored the experience of participating in a holistic neuropsychological rehabilitation programme by conducting three focus groups with twelve former clients who had sustained a brain injury. Data were transcribed verbatim and analysed using thematic analysis. "It is an ongoing process" emerged as the overarching theme for the experience of recovery from brain injury. Four subthemes, or phases, were identified. Participants went through (1) a phase of confrontation, after which they (2) trained their skills and strategies, and (3) experimented with these in daily life. In the end, clients reached a phase of (4) coming to terms with their injury. Participants described increased levels of self-esteem, sense of competence, and adaptation as the most important outcomes of the programme, as these factors helped them regain a sense of identity. The results indicate that including these factors in outcome evaluations of complex interventions after brain injury may be important as they appear essential for capturing the client's perspective on change.